2021
DOI: 10.1371/journal.pone.0258930
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of first-line antiretroviral treatment failure among adult patients on treatment in Mettu Karl Specialized Hospital, South West Ethiopia; a case control study

Abstract: Background Antiretroviral therapy has dramatically reduced Human Immunodeficiency Virus related morbidity and mortality. It has also transformed HIV infection into a manageable chronic condition. However, first-line antiretroviral treatment failure continues to grow especially in resource limited settings. Despite this, determinants of first-line antiretroviral treatment failure are not well studied in Ethiopia. Objective To identify determinants of first-line antiretroviral treatment failure among adult pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…According to our data, patients with CD4 < 200 cells/mm were 41 times more likely to experience virological failure than were those with CD4 ≤ 200 cells/mm (OR = 41, P < 0.001). In line with our findings, another study reported that the probability of viral treatment failure is nine times greater in these patients than in those with higher CD4 T-cell counts [ 51 – 54 ]. A high level of HIV replication indicates a decreased CD4 + T-cell count and poor immune responses, leading to virological failure [ 55 ].…”
Section: Discussionsupporting
confidence: 92%
“…According to our data, patients with CD4 < 200 cells/mm were 41 times more likely to experience virological failure than were those with CD4 ≤ 200 cells/mm (OR = 41, P < 0.001). In line with our findings, another study reported that the probability of viral treatment failure is nine times greater in these patients than in those with higher CD4 T-cell counts [ 51 – 54 ]. A high level of HIV replication indicates a decreased CD4 + T-cell count and poor immune responses, leading to virological failure [ 55 ].…”
Section: Discussionsupporting
confidence: 92%
“…Patients who had a longer duration of stay on ART had a higher risk of developing virological failure. similarly, previous studies conducted in Waghimra, Northern Ethiopia, and Mettu, South West Ethiopia [ 22 , 86 ] revealed that patients who had been on ART for a longer time were more susceptible to developing virological failure. The possible explanation might be due to the prolonged use of ART, which can increase the risk of developing poor adherence to treatment and unfavorable medication reactions [ 26 ].…”
Section: Discussionmentioning
confidence: 59%
“…Furthermore, HIV viral load suppression is the most important indicator of successful antiretroviral therapy, progression, and death, as well as the most effective monitoring strategy for confirming a diagnosis and proving ARV treatment failure [ 21 ]. Despite the expanded availability of antiretroviral treatment (ART) around the world, virological failure remains a significant challenge for HIV patients [ 22 , 23 ]. Delays in commencing ART can have serious consequences, particularly for people with tuberculosis or extensive immunosuppression who are at high risk of mortality [ 21 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Late initiation of ART (>30 days) did not appear to be associated with a greater likelihood of VTF (HR: 0.91[95% CI: 0.67-1.27]), contrary to studies affirming the importance of early treatment [48,49]. It may be that an impaired immune system as indicated by the occurrence of OIs, better reflects the risk of developing VTF, rather than late ART initiation.…”
Section: Plos Global Public Healthmentioning
confidence: 67%